Wage Determination and Incomes Policy in Open Economies - Braun, Anne (International Monetary Fund, 1986)
Written by Anne Romanis Braun, a former staff member of the IMF's Research Department, this volume deals with the nature of wage determination and the problem of securing an economically appropriate development of money incomes in an open economy over the medium term.